The feeding response of white-bellied sunbirds (Cinnyris [Nectarinia] talatala) to sugar concentration and viscosity of artificial nectar - Nicolson, Sue W. (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2010.